Correlation of energy intake and physical activity with visceral fat in obese office - Fika Dwi Sasri; Fiastuti Witjaksono; Nani Cahyani Sudarsono (World Nutrition Journal, 2023)
Background: Obesity is a global health problem with a continuing trend of increasing population. A positive energy balance, where energy intake is more remarkable than energy expenditure, will cause fat accumulation. Obesity due to the expansion of fat, especially visceral fat, is a risk factor for noncommunicable diseases. Office employees can become obese with a high-calorie diet and a sedentary lifestyle. This study aims to determine the correlation between energy intake and physical activity with visceral fat in obese office workers. Methods: This cross-sectional study was conducted on obese office staff at RSCM. Energy intake was assessed with 3 x 24-h food recalls. Physical activity was assessed with the GPAQ questionnaire, and visceral fat was considered with multifrequency BIA. Results: A total of 66 study subjects with an average age of 41 years were women and included in the category of obesity degree I. Almost all subjects had abnormal visceral fat volume with a median of 2.95 L (1.3 – 8.5 L). Most have more energy intake, with an average intake of 2196 ± 467 kcal. Most had moderate physical activity with a median value of 1850 MET (120 – 4680 MET). There was a moderate correlation between energy intake and visceral fat (r=0.554, p<0.001) and a weak correlation between physical activity and visceral fat (r=-324, P=0.008). Conclusion: There was a moderate correlation between energy intake and visceral fat and a weak correlation between physical activity and visceral fat.